A life cycle assessment of a 'minus carbon' refugee house: global warming potential and sensitivity analysis. (27th April 2020) - Dabaieh, Marwa; Emami, Nargessadat; Heinonen, Jukka Taneli; Marteinsson, Björn
Abstract : Purpose: Over the last eight years, the Middle East has experienced a series of high profile conflicts which have resulted in over 5.6 million Syrians forced to migrate to neighbouring countries within the MENA (Middle East and North Africa) region or to Europe. That have exerted huge pressure on hosting countries trying to accommodate refugees in decent shelters and in quick manner. Temporary shelters normally carry a high environmental burden due to their short lifespan, and the majority are fabricated from industrialised materials. This study assesses the carbon impact for a minus carbon experimental refugee house in Sweden using life cycle assessment (LCA) as tool. SimaPro and GaBi software were used for the calculations and the ReCiPe midpoint method for impact assessment. The results show that using local plant-based materials such as straw, reeds and wood, together with clay dug from close to the construction site, can drastically reduce the carbon footprint of temporary shelters and even attain a negative carbon impact of 226.2 kg CO2 eq/m 2 . Based on the results of the uncertainty importance analysis, the overall global warming potential impact without and with sequestration potential are mostly sensitive to the variability of the GWP impact of wood fibre insulation. Design/methodology/approach: The methodology is designed to calculate the GWP impact of the refugee house over its entire life cycle (production, operation and maintenance and end of life). Then, the sensitivity analysis was performed to explore the impact of input uncertainties (selection of material from the database and the method) on the total GWP impact of the refugee house with and without sequestration. The ISO standards (International Standard 14040 2006; International Standard 14044 2006) divide the LCA framework into four steps of Goal and scope, inventory analysis, impact assessment, and interpretation. Findings: This study has shown an example for proof of concept for a low impact refugee house prototype using straw, reeds, clay, lime and wood as the principle raw materials for building construction. Using natural materials, especially plant-based fibres, as the main construction materials, proved to achieve a minus carbon outcome over the life cycle of the building. The GWP of the shelter house without and with sequestration are found to be 254.7 kg CO2 eq/m 2 and -226.2 kg CO2 eq/m 2, respectively. Originality/value: As there are still very few studies concerned with the environmental impact of temporary refugee housing, this study contributes to the pool of knowledge by introducing a complete LCA calculation for a physical house prototype as a proof of concept on how using low impact raw materials for construction combined with passive solutions for heating and cooling can reach a minus carbon outcome. The GWP of the shelter house without and with sequestration are found to be 254.7 kg CO2 eq/m 2 and -226.2 kg CO2 eq/m 2 .